AKTIVA TETAP DALAM NERACA DAN BELANJA MODAL PADA ANGGARAN PENDAPATAN DAN BELANJA DAERAH (Studi Analisis Kualitatif Di Kantor Walikota Jayapura) - John Agustinus (Jurnal Analisis Manajemen, 2011)
Within the context of debates about integrated and territorial approaches to rural development in Indonesia regions, this paper introduces the notion of integrated rural theorized in relation to the concepts of embeddedness, dis-embeddedness, endogeneity, and empowerment. The paper reports on qualitative research which explored the existence of such characteristics in rural networks operating among small businesses and resource controllers in the Jayapura. It is argued that the creation of embedded and endogenous networks does not necessarily result in empowerment for all concerned. Complex issues of participation and inclusion remain central to the creation of equitable, sustainable, and integrated rural.